Prospective monitoring of after‐hours nursing and technologist support calls to a regional Canadian home hemodialysis program. Issue 1 (5th October 2018) - Reintjes, Frances; Herian, Nim; Shah, Nikhil; Pauly, Robert P.
Abstract: Introduction: Increasing renal care providers offer home hemodialysis (HD) as a modality choice. There is considerable variation in the provision of after‐hours on‐call support for self‐dialyzing patients and no literature describing the utility of this service. In this prospective, observational study we sought to monitor and classify the number and nature of interactions between home patients and our on‐call nurses and technologists, and enumerate the number of adverse events averted by the availability of on‐call staff. Methods: Our home HD unit provided 24‐hour on‐call patient support and during a 4‐month period in 2012, we prospectively monitored all patient calls to this service. The nature of the calls was logged as nursing‐related vs. technical. Call outcomes were classified according to whether patients were able to initiate/resume their treatments or whether additional interventions were required. Findings: During this period, our program cared for 58 home HD patients. Nurses fielded 172 calls and dealt with 239 issues. One hundred nine (46%) were clinical issues including 5 (2%) of a serious nature involving potential harm; 67 (28%) related to machine setup or alarms, 36 (15%) required a technologist to resolve, and 27 (11%) were deemed non‐urgent. One hundred six issues were directed to technologists in 99 calls. Issues pertained to machine malfunction (45 calls—43%), machine set‐up and alarms (25 calls—24%), or the water system (24 calls—23%). Only 12 calls (11.3%) were not of a technical nature. Nursing and technologist support allowed patients to initiate or continue their treatment 75% and 71% of the time, respectively. Discussion: Home HD on‐call services provide patients support to successfully continue their dialysis treatments by troubleshooting clinical and technical aspects of dialysis and by averting potential adverse events.